Development of Information Systems E-People Sarawak at CV. Mobilus Interactive: Development of Information Systems E-People Sarawak at CV. Mobilus Interactive - Rieska Rahayu Ayuningsih; Iis Ismayanti (Jurnal Mantik, 2020)
The development of information systems in an area extremely influential, as dengna development of the technological age has become something that is desperately needed by the people particularly the region of Sarawak which is always improving communications services therefore dibagunlah application of E-Rakyat Sarawak where the public can report a wide range of issues going on around it and the government will identify and handle problems that occur with more quickly.In addition also their E-these people can help the community in Sarawak to be able to see on the places that can be addressed to any problems reported through the Information Systems E-Rakyat Sarawak.